Markups, Gaps, and the Welfare Costs of Business Fluctuations - Galí, Jordi; Gertler, Mark; López-Salido, J. David (The Review of Economics and Statistics, 2007)
In this paper we present a simple, theory-based measure of the variations in aggregate economic efficiency associated with business fluctuations. We decompose this indicator, which we refer to as "the gap", into two constituent parts: a price markup and a wage markup, and show that the latter accounts for the bulk of the fluctuations in our gap measure. Finally, we derive a measure of the welfare costs of business cycles that is directly related to our gap variable, and which takes into account explicitly the existence of a varying aggregate inefficiency. When applied to postwar U.S. data, for plausible parametrizations, our measure suggests welfare losses of fluctuations that are of a higher order of magnitude than those derived by It also suggests that the major postwar recessions involved substantial efficiency costs.